Canva Application for Learning Fiqh Subjects in Grade V of SDI Matsaratul Huda Panempan Pamekasan - Moh. Mahfud; Nur Kholis; M Yunus Abu Bakar (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This research aims to develop a Canva-based audiovisual learning media application for the subject of Fiqh in the fifth grade of SDI Matsaratul Huda Panempan Pamekasan. The method used in this research is a development research approach consisting of initial analysis, material identification, product development, and testing stages. After the product is developed, experts evaluate its suitability by assessing the media design, content alignment, design completeness, and attractiveness. The expert assessment results show that the Canva-based audiovisual learning media design obtains a score of 83 percent, categorizing it as good. Limited student feedback also indicates a score of 77,13 percent, categorizing it as good. Based on the assessments from both experts and students, it can be concluded that this Canva-based audiovisual learning media is suitable for use in the experimental school. The field trial results indicate a score of 66,25 percent in the first cycle and 81 percent in the second cycle. The percentage increase in student learning outcomes shows that they have a better understanding of Fiqh subjects when using audiovisual learning media based on the Canva application which has good criteria. Therefore, this developed media can be used for both online and offline learning.